2016
DOI: 10.1108/jmlc-05-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Internal audit function and AML compliance: the globalisation of the internal audit function

Abstract: Purpose This paper aims to consider the role of internal audit function (IAF) in relation to anti-money laundering (AML) compliance and oversight within global banking. The increasing globalisation of banking functions and the mirrored globalisation of financial crime require a renewed look at the role of internal audit. This paper critically examines the weaknesses in the current structure and proposes a new way of thinking about IAF. Design/methodology/approach The paper uses secondary data to analyse the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
(30 reference statements)
0
26
0
4
Order By: Relevance
“…Finally, we controlled for the sector and size of the IAF. The financial sector is highly regulated, which can influence the activities performed by the IAF (Gras-Gil et al, 2012;Koutoupis and Tsamis, 2009;Naheem, 2016). The sector in which organisations operate was, therefore, included as a control variable.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we controlled for the sector and size of the IAF. The financial sector is highly regulated, which can influence the activities performed by the IAF (Gras-Gil et al, 2012;Koutoupis and Tsamis, 2009;Naheem, 2016). The sector in which organisations operate was, therefore, included as a control variable.…”
Section: Methodsmentioning
confidence: 99%
“…Competency. Previous studies (Mat Zain et al, 2015;Naheem, 2016) have discussed the attributes of an auditor and found that the internal auditor's capability of solving problems is a sign of audit efficiency. It has also been found that expertize can reduce the influence of irrelevant factors on the judgment of an auditor.…”
Section: Internal Sharīʿah Audit Effectivenessmentioning
confidence: 99%
“…Bhaskar, Schroeder, and Shepardson (2019) look into the duplication of external audit with internal checks (internal audit) and provide evidence that internal checks are more likely to reveal significant discrepancies. This implies the distinctive main roles of external audit (to increase the reliability of financial statements published by the company management) and internal audit (to ensure the effective functioning of the company based on good organization of work, which is conditional on functional internal organizational structure, economy of operation, property protection, and effective use of funding sources (Kafka, 2009;Naheem, 2016;Raiborn, 2017). The aforementioned types of audit also differ in the user base.…”
Section: Literature Reviewmentioning
confidence: 99%